Closeness, distance and disappearances in Cameroonian mediated transnational social ties: Uses of mobile phones and narratives of transformed identities. (1st March 2017) - Tazanu, Primus M.; Frei, Bettina Anja
Drawn from ethnographic fieldwork conducted among Cameroonians in Switzerland, Germany, and Cameroon, this article demonstrates transformations induced by the new communication media − particularly the mobile phone – in Cameroonian transnational social relationships. Many narratives revolve around ambivalences, tensions and non-communication that arise from different and often, contradictory expectations as well as dissimilar life-world experiences of the actors. We employ the notion of an ideal 'African sociality' to serve as guideline for the valuations of the mediated ties, which is reflected in, and opposed to the notion of migrant or 'bushfaller disease' – migrants' attributive tendency to detach from these ideals when abroad. In these narratives, technological means for communication and related users' agency serve as catalyst through which changing sociality is observed and articulated by migrants abroad and non-migrants in Cameroon.